Deregulated bile acids may drive hepatocellular carcinoma metastasis by inducing an immunosuppressive microenvironment - Xia, Jin-kun; Tang, Ning; Wu, Xing-yu; Ren, Hao-zhen (Frontiers in Oncology, 2022)
Bile acids (BAs) are physiological detergents that can not only promote the digestion and absorption of lipids, but also may be a potential carcinogen. The accumulation of BAs in the body can lead to cholestatic liver cirrhosis and even liver cancer. Recently, studies demonstrated that BAs are highly accumulated in metastatic lymph nodes, but not in normal healthy lymph nodes or primary tumors. Lymph node metastasis is second only to hematogenous metastasis in liver cancer metastasis, and the survival and prognosis of hepatocellular carcinoma (HCC) patients with lymph node metastasis are significantly worse than those without lymph node metastasis. Meanwhile, component of BAs was found to significantly enhance the invasive potential of HCC cells. However, it is still poorly understood how deregulated BAs fuel the metastasis process of liver cancer. The tumor microenvironment is a complex cellular ecosystem that evolves with and supports tumor cells during their malignant transformation and metastasis progression. Aberrant BAs metabolism were found to modulate tumor immune microenvironment by preventing natural killer T (NKT) cells recruitment and increasing M2-like tumor-associated macrophages (TAMs) polarization, thus facilitate tumor immune escape and HCC development. Based on these available evidence, we hypothesize that a combination of genetic and epigenetic factors in cancerous liver tissue inhibits the uptake and stimulates the synthesis of BAs by the liver, and excess BAs further promote liver carcinogenesis and HCC metastasis by inducing immunosuppressive microenvironment.